A high-entropy perovskite-type absorber coating with ultra-broadband electromagnetic wave absorption properties
By adopting high-entropy perovskite type absorption coating, the problem that existing photothermal materials do not absorb extensively and easily oxidize electromagnetic waves at high temperatures is solved, and the efficient absorption of ultra-wide electromagnetic waves and good oxidation resistance is achieved, which is suitable for high-temperature solar energy and industrial waste heat collection.
Patent Information
- Application Number
- CN202410271593.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-03-11
AI Technical Summary
The absorption of electromagnetic waves by existing photothermal materials is mainly concentrated in a specific narrow band and is easily oxidized. It is not suitable for high-temperature applications and is difficult to meet the needs of solar energy and industrial waste heat at the same time.
A high-entropy perovskite type absorption coating is adopted, which consists of high-entropy perovskite ceramic pigment, and the molecular formula is ABO3, where A is any five elements in La, Pr, Ca, Ce, Gd, Sm, Nd, Nb, and Dy, and B is one of Cr, Co, Mn, Fe, and Al. It is prepared by ball mill mixing, drying, calcining and other processes to form a coating with ultra-wideband electromagnetic wave absorption characteristics.
It has achieved high efficiency absorption rate (not less than 0.92) for electromagnetic waves in the ultra-wide band of 0.3-2.5μm sunlight and 0.3-16μm ultra-wide band at a high temperature of 800-1500℃, and has good oxidation resistance. It is suitable for high-temperature concentrated solar power generation systems and industrial waste heat collection.
Smart Images

Figure CN118146658B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electromagnetic wave absorption, and in particular to a high entropy perovskite type absorption coating with ultra-wideband electromagnetic wave absorption characteristics. Background Art
[0002] With the continuous reduction of fossil fuel reserves, the necessity of exploring sustainable alternatives for energy production is increasing, and the efficient collection and utilization of solar energy and the collection of industrial waste heat (infrared radiation) are effective ways to solve the above problems. At present, the utilization of solar energy and the collection of infrared radiation energy through the photothermal effect are concentrated in the field of high-temperature applications. However, the absorption of electromagnetic waves by traditional photothermal materials (such as nanocarbon, metal nanomaterials, sulfides and carbides) is mainly concentrated in a specific narrow band, and they are easily oxidized and are not suitable for high-temperature applications. Although light-absorbing materials manufactured by electrochemical etching, photolithography and physical vapor deposition techniques can meet the requirements of wide-band absorption, they are mainly composed of nanostructures, and the preparation process is very expensive and cannot meet the actual needs of large-scale production. Although metal oxides (CuO, Fe 2 O 3 、Ni x O y etc.) can be used in oxygen-rich high-temperature environments, but their electromagnetic wave absorption band is relatively narrow and their absorption coefficient is low. Therefore, in order to simultaneously meet the needs of solar energy and industrial waste heat collection, it is crucial to develop materials that can meet the ultra-wide electromagnetic wave (ultraviolet, visible light, infrared region) absorption characteristics and exhibit excellent antioxidant properties at high temperatures.
[0003] Lanthanide perovskite composite oxides are particularly suitable for high-temperature applications due to their stable structure, high melting point and excellent high-temperature oxidation resistance. The general formula of this material is ABO 3 , where A is La coordinated with 12 oxygen atoms, mainly used to stabilize the perovskite structure, and B is usually composed of transition metal elements (Cr, Mn, Fe, Co, Ni, Cu, Ti, etc.), coordinated with 6 oxygen atoms and in BO 6 Hexahedral center. This crystal structure has high symmetry, unique spatial charge distribution, and abundant covalent bonds. LaCrO 3 、LaFeO 3 、LaMnO 3 It has been shown that lanthanide perovskites have good solar absorption properties. However, the single lanthanide perovskite has a wide band gap, which limits the optical absorption properties over the ultra-wide electromagnetic spectrum (ultraviolet, visible light, infrared region). Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a high-entropy perovskite-type absorption coating with good performance and ultra-wideband electromagnetic wave absorption characteristics.
[0005] In order to solve the above problems, the present invention discloses a high entropy perovskite type absorption coating with ultra-wideband electromagnetic wave absorption characteristics, characterized in that the absorption coating is composed of the following raw materials in parts by mass: 8 to 16 parts of absorption pigment, 2 to 4 parts of filler, 20 to 40 parts of binder, 22 to 65 parts of ultrapure water, and 10 to 15 parts of additives; the light-absorbing pigment is a high entropy perovskite ceramic pigment, and its molecular formula is ABO 3 , wherein A is any five elements of La, Pr, Ca, Ce, Gd, Sm, Nd, Nb, and Dy, and each metal element is in an equal molar ratio; B is one of the metal elements Cr, Co, Mn, Fe, and Al.
[0006] The coating has a thickness of 50-100 μm, an operating temperature range of 800-1500°C, an absorptivity of not less than 0.95 in the 0.3-2.5 μm band of sunlight, and an absorptivity of not less than 0.92 in the 0.3-16 μm ultra-wide band.
[0007] The absorption pigment is a powder material with a perovskite crystal structure and a diameter of 50-600 nm, and its absorption rate in the 0.3-2.5 μm band of sunlight is not less than 0.87, and its absorption rate in the 0.3-16 μm ultra-wideband band is not less than 0.85.
[0008] The absorbing pigment is prepared by the following method: AO with a molar ratio of metal elements of 1:1 x Powder and BO x The powder is used as the raw material for ball milling and mixing, and the mixture powder is obtained after drying and grinding; the mixture powder is calcined at high temperature in an air atmosphere, cooled and ground to obtain the AO x CaO, Pr 6 O 11 ,La 2 O 3 、Ce 2 O 3 、Nd 2 O 3 、Sm 2 O 3 , Nb 2 O 3 , Gd 2 O 3 、Dy 2 O 3 Any five of the powders; the BO x Cr 2 O 3 、CoO、MnO 2 , Fe 2 O 3 、Al 2 O 3 Any one of .
[0009] The ball milling mixing conditions refer to using a planetary ball mill for wet ball milling, a ball milling speed of 300-500 r / min, a ball milling time of 5-12 hours, and a ball-to-material-water mass ratio of 2-5:1:3.
[0010] The high temperature calcination conditions refer to a calcination temperature of 900-1500°C, a heating rate of 3-10°C / min, and a calcination time of 2-6 hours; the cooling method is one of furnace cooling, air quenching cooling, and liquid nitrogen quenching cooling.
[0011] The filler is one or more of calcium carbonate, porous powdered quartz, white carbon black, mica powder and bentonite, and the particle size is 50-200 nm.
[0012] The binder is at least one of rare earth phosphate, aluminum phosphate and titanium phosphate.
[0013] The auxiliary agent is a mixture of a leveling agent, a dispersant and a defoamer in a mass ratio of 1:1:1 to 1:2:3; the leveling agent is one or two of Deqian 810 silicone leveling agent-polyether modified polysiloxane, AFCONA-3587-polyether modified silicone, and AFCONA-3085-polyether modified silicone; the dispersant is sodium oleate C 17 H 33 COONa, carboxylates, sulfates (RO-SO 3 Na), sulfonate (R-SO 3 Na) one or more; the defoaming agent is TEGOAntifoam 3062 polyether defoaming agent, AFCONA-2035-fluorocarbon modified silicone, AFCONA-2040-fluorocarbon modified silicone machine one or two.
[0014] The method for preparing a high entropy perovskite type absorption coating having ultra-wideband electromagnetic wave absorption characteristics as described above comprises the following steps:
[0015] ⑴Weigh according to the ratio;
[0016] (2) After the ultrapure water, binder and additives are evenly mixed and dispersed, the absorbing pigment and filler are added, and a high-speed disperser is used to stir at a speed of 600-1200 r / min for 60-100 min, and then a sand mill or a ball mill is used to disperse and grind to a fineness of 15-30 μm; finally, a 100-200 mesh screen is used to filter to obtain an ultra-wideband electromagnetic wave absorbing perovskite-type high entropy absorbing coating;
[0017] ⑶ Substrate surface treatment: Use quartz stone or brown corundum with a particle size of 1~5μm to sandblast the substrate surface to make the surface cleanliness of the substrate reach Sa 2.5~3.0 level requirements;
[0018] (4) Under the condition of ambient temperature of 15-30℃ and relative air humidity below 85%, use 0.8MPa compressed air to spray ultra-wideband electromagnetic wave absorbing perovskite-type high entropy absorption coating on the treated substrate surface twice. After spraying, let it stand for 48 hours and then heat up in the furnace to cure, thus obtaining ultra-wideband electromagnetic wave absorbing coating.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. In the present invention, the A position of the perovskite compound is a rare earth or alkaline earth metal ion (with a valence of + 2 and + 3), and the B position is a transition metal ion (with a valence of + 3, + 4 and + 5). When the A position ions in the high entropy light-absorbing pigment are replaced by multiple metal ions, oxygen vacancies and multivalent states are formed, which enhances free carrier absorption and lattice vibration absorption.
[0021] 2. The light-absorbing pigments in the high-entropy perovskite-type absorption coating obtained by the present invention contain a variety of rare earth and transition metal elements. The rare earth elements contain a plurality of unfilled 4f electrons and the transition metals contain a plurality of unfilled 3d electron transitions, which can absorb light of different wavelengths from ultraviolet, visible to infrared light regions, thereby showing ultra-wideband electromagnetic wave absorption capacity. In addition, the introduction of a plurality of impure energy levels by a plurality of rare earth elements and transition metal elements is conducive to reducing the band gap, thereby improving the material's absorption capacity for electromagnetic waves in the infrared region.
[0022] 3. The coating obtained by the present invention has the characteristics of high temperature corrosion resistance (operating temperature up to 1500°C). The binder of the coating is at least one of rare earth phosphate, aluminum phosphate, and titanium phosphate, and has good high temperature resistance. In addition, the high configuration entropy of the high entropy material enhances high temperature thermal stability. The coating obtained by the present invention is prepared on refractory bricks and cured at room temperature for 24 hours; then, it is calcined at 1500°C for 48 hours, and the surface of the refractory bricks is observed. The results show that there is no obvious bubbling, cracking, shedding and other phenomena, indicating that the coating has good high temperature resistance.
[0023] 4. The thermal expansion coefficient of the coating obtained by the present invention is highly matched with that of the substrate. The coating is made of raw materials such as perovskite high entropy ceramics, porous powdered quartz, white carbon black, calcium carbonate, bentonite, etc., and the percentage between the raw material components can be adjusted to make the coating and the substrate have matching thermal expansion coefficients. The matching thermal expansion coefficient allows the coating to be closely attached to the surface of the substrate, and the coating does not fall off or crack, effectively protecting the substrate and preventing oxidation, wear and high-temperature corrosion of the substrate.
[0024] 5. The present invention is simple to operate and has high production efficiency. It can prepare a coating with an operating temperature range of 800 to 1500°C without complicated post-processing. The absorptivity in the 0.3 to 2.5 μm band of sunlight is not less than 0.95, and the absorptivity in the 0.3 to 16 μm ultra-wide band is not less than 0.92. The coating can be used in high-temperature concentrated solar power generation systems and industrial waste heat collection. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0026] Figure 1 For Example 1 of the present invention (La 0.2 Pr 0.2 Ca 0.2 Nd 0.2 Sm 0.2 )CrO 3 XRD pattern of .
[0027] Figure 2 For Example 2 of the present invention (Sm 0.2 G 0.2 Ce 0.2 Nb 0.2 Dy 0.2 )CoO 3 XRD pattern of .
[0028] Figure 3 For Example 2 of the present invention (Sm 0.2 G 0.2 Ce 0.2 Nb 0.2 Dy 0.2 )CoO 3 Solar absorption spectrum in the 0.3 ~ 2.5 μm band.
[0029] Figure 4 For Example 2 of the present invention (Sm 0.2 G 0.2 Ce 0.2 Nb 0.2 Dy 0.2 )CoO 3 Absorption spectrum in the 0.3 ~ 16μm band.
[0030] Figure 5 Example 3 (La 0.2 Pr 0.2 Ca 0.2 Ce 0.2 G 0.2 )FeO 3 XRD pattern of .
[0031] Figure 6For Example 4 of the present invention (La 0.2 Sm 0.2 Ca 0.2 G 0.2 Dy 0.2 )AlO 3 XRD pattern of .
[0032] Figure 7 Example 5 (La 0.2 Sm 0.2 Ca 0.2 G 0.2 Dy 0.2 )MnO 3 XRD pattern of . DETAILED DESCRIPTION
[0033] A high entropy perovskite type absorption coating with ultra-wideband electromagnetic wave absorption characteristics, the absorption coating is composed of the following raw materials in mass parts (g): 8-16 parts of absorption pigment, 2-4 parts of filler, 20-40 parts of binder, 22-65 parts of ultrapure water, and 10-15 parts of additives. The thickness of the coating is 50-100 μm, the operating temperature range is 800-1500°C, the absorption rate in the 0.3-2.5 μm band of sunlight is not less than 0.95, and the absorption rate in the ultra-wide band range of 0.3-16 μm is not less than 0.92.
[0034] The preparation method thereof comprises the following steps:
[0035] ⑴Weigh according to the ratio;
[0036] (2) After the ultrapure water, binder and additives are evenly mixed and dispersed, the absorbing pigment and filler are added, and a high-speed disperser is used to stir at a speed of 600-1200 r / min for 60-100 min, and then a sand mill or a ball mill is used to disperse and grind to a fineness of 15-30 μm; finally, a 100-200 mesh screen is used to filter to obtain an ultra-wideband electromagnetic wave absorbing perovskite-type high entropy absorbing coating;
[0037] ⑶ Substrate surface treatment: Use quartz stone or brown corundum with a particle size of 1~5μm to sandblast the substrate surface to make the surface cleanliness of the substrate reach Sa 2.5~3.0 level requirements;
[0038] (4) Under the condition of ambient temperature of 15-30℃ and relative air humidity below 85%, use 0.8MPa compressed air to spray ultra-wideband electromagnetic wave absorbing perovskite-type high entropy absorption coating on the treated substrate surface twice. After spraying, let it stand for 48 hours and then heat up in the furnace to cure, thus obtaining ultra-wideband electromagnetic wave absorbing coating.
[0039] Among them: the light-absorbing pigment is a high entropy perovskite ceramic pigment, and its molecular formula is ABO 3, wherein A is any five elements of La, Pr, Ca, Ce, Gd, Sm, Nd, Nb, and Dy, and each metal element is in an equal molar ratio; B is one of the metal elements Cr, Co, Mn, Fe, and Al. The absorbing pigment is a powder material with a perovskite crystal structure and a diameter of 50 to 600 nm, and its absorption rate in the 0.3 to 2.5 μm band of sunlight is not less than 0.87, and its absorption rate in the 0.3 to 16 μm ultra-wideband band is not less than 0.85.
[0040] The absorbing pigment is prepared by the following method: AO with a molar ratio of 1:1 of metal elements x Powder and BO x Powder as raw material, AO x CaO, Pr 6 O 11 ,La 2 O 3 、Ce 2 O 3 、Nd 2 O 3 、Sm 2 O 3 , Nb 2 O 3 , Gd 2 O 3 、Dy 2 O 3 Any five of the powders; BO x Cr 2 O 3 、CoO、MnO 2 , Fe 2 O 3 、Al 2 O 3 Any one of the above. The above powder is wet-milled by a planetary ball mill, the ball milling speed is 300~500r / min, the ball milling time is 5~12 hours, and the mass ratio of ball material to water (g / g) is 2~5:1:3. Ball milling process: first ball mill for 1 hour, then pause for 10 minutes, then ball mill for 1 hour, pause for 10 minutes, and repeat the ball milling cycle. After ball milling and mixing, the mixture powder is obtained after drying and grinding; the mixture powder is calcined at high temperature in an air atmosphere, the calcination temperature is 900~1500℃, the heating rate is 3~10℃ / min, and the calcination time is 2~6 hours. After calcination, it is cooled and ground by one of the methods of furnace cooling, air quenching cooling and liquid nitrogen quenching cooling to obtain.
[0041] The filler is one or more of calcium carbonate, porous powdered quartz, white carbon black, mica powder and bentonite, with a particle size of 50-200 nm. These fillers can reduce the cost of the coating, increase the coating thickness, and enhance the hardness and wear resistance of the coating.
[0042] The binder is at least one of rare earth phosphate, aluminum phosphate and titanium phosphate.
[0043] The additive is a mixture of leveling agent, dispersant and defoamer in a mass ratio of 1:1:1 to 1:2:3 (g / g). The leveling agent is one or two of Deqian 810 silicone leveling agent-polyether modified polysiloxane, AFCONA-3587-polyether modified silicone, AFCONA-3085-polyether modified silicone; the dispersant is sodium oleate C 17 H 33 COONa, carboxylates, sulfates (RO-SO 3 Na), sulfonate (R-SO 3 Na) one or more; the defoaming agent is TEGO Antifoam 3062 polyether defoaming agent, AFCONA-2035-fluorocarbon modified silicone, AFCONA-2040-fluorocarbon modified silicone machine one or two.
[0044] Example 1 A high entropy perovskite-type absorption coating with ultra-wideband electromagnetic wave absorption characteristics is composed of the following raw materials: 8g absorption pigment, 2g filler, 20g binder, 22g ultrapure water, and 10g auxiliary agent.
[0045] The method for preparing the coating comprises the following steps:
[0046] ⑴Weigh according to the ratio;
[0047] ⑵ After the ultrapure water, binder and additives are evenly dispersed, add the absorbing pigment (La 0.2 Pr 0.2 Ca 0.2 Nd 0.2 Sm 0.2 )CrO 3 (The XRD spectrum of the pigment is as follows Figure 1 As shown in the figure, and fillers are first stirred at a speed of 600-1200 r / min for 60-100 min using a high-speed disperser, and then dispersed and ground to a fineness of 15-30 μm using a sand mill or a ball mill; finally, filtered with a 100-200 mesh screen to obtain an ultra-wideband electromagnetic wave absorbing perovskite-type high entropy absorbing coating;
[0048] ⑶ Substrate surface treatment: Use quartz stone or brown corundum with a particle size of 1~5μm to sandblast the substrate surface to make the surface cleanliness of the substrate reach Sa 2.5~3.0 level requirements;
[0049] (4) Under the conditions of an ambient temperature of 15 to 30°C and a relative air humidity of less than 85%, 0.8 MPa compressed air was used to spray the ultra-wideband electromagnetic wave absorbing perovskite-type high entropy absorbing coating on the treated substrate surface twice. After spraying, it was allowed to stand for 48 hours and then cured with the furnace heating to obtain an ultra-wideband electromagnetic wave absorbing coating with a thickness of 50 to 100 μm.
[0050] Wherein: the absorbing pigment is prepared by the following method: AO with a molar ratio of metal elements of 1:1 x Powder and BO x Powder as raw material, AO x For La 2 O 3 , Pr 6 O 11 , CaO, Nd 2 O 3 、Sm 2 O 3 Powder;BO x Cr 2 O 3 Powder. The above powder is wet-milled in a planetary ball mill, the ball milling speed is 300~500 r / min, the ball milling time is 5~12 hours, and the mass ratio of ball material to water (g / g) is 2~5:1:3. Ball milling process: first ball mill for 1 hour, then pause for 10 minutes, then ball mill for 1 hour, pause for 10 minutes, and repeat the ball milling cycle. After ball milling and mixing, the mixture powder is obtained after drying and grinding; the mixture powder is calcined at high temperature in an air atmosphere, the calcination temperature is 900~1500℃, the heating rate is 3~10℃ / min, and the calcination time is 2~6 hours. After calcination, it is cooled and ground by one of the methods of furnace cooling, air quenching cooling and liquid nitrogen quenching cooling to obtain.
[0051] The performance indicators of the obtained coatings are shown in Table 1.
[0052] Table 1 Performance indicators
[0053]
[0054] Example 2 A high entropy perovskite-type absorption coating with ultra-wideband electromagnetic wave absorption characteristics is composed of the following raw materials: 16 g absorption pigment, 4 g filler, 40 g binder, 65 g ultrapure water, and 15 g auxiliary agent.
[0055] The coating is prepared in the same manner as in Example 1. 0.2 G 0.2 Ce 0.2 Nb 0.2 Dy 0.2 )CoO 3XRD spectra and absorption spectra in the 0.3~2.5 μm and 0.3~16 μm bands, such as Figure 2 , Figure 3 and Figure 4 shown.
[0056] Wherein: the light absorbing pigment is prepared according to the method described in Example 1, but its raw material is AO with a molar ratio of metal elements of 1:1 x Powder and BO x Powder, AO x Sm 2 O 3 , Gd 2 O 3 、Ce 2 O 3 、Dy 2 O 3 , Nb 2 O 5 Powder;BO x It is CoO powder.
[0057] The performance indicators of the obtained coatings are shown in Table 2.
[0058] Table 2 Performance indicators
[0059]
[0060] Example 3 A high entropy perovskite-type absorption coating with ultra-wideband electromagnetic wave absorption characteristics is composed of the following raw materials: 12 g absorption pigment, 3 g filler, 30 g binder, 44 g ultrapure water, and 13 g auxiliary agent.
[0061] The coating is prepared in the same manner as in Example 1. 0.2 Pr 0.2 Ca 0.2 Ce 0.2 G 0.2 )FeO 3 The XRD spectrum of Figure 5 shown.
[0062] Wherein: the absorbing pigment is prepared according to the method described in Example 1, but its raw material is AO with a molar ratio of metal elements of 1:1 x Powder and BO x Powder, AO x For La 2 O 3 , Pr 6 O 11 , CaO, Ce 2 O 3 , Gd 2 O 3 Powder;BO xFe 2 O 3 powder.
[0063] The coating performance indicators are shown in Table 3.
[0064] Table 3 Performance indicators
[0065]
[0066] Example 4 A high entropy perovskite-type absorption coating with ultra-wideband electromagnetic wave absorption characteristics is composed of the following raw materials: 10 parts of absorption pigment, 2.5 parts of filler, 25 parts of binder, 35 parts of ultrapure water, and 12 parts of additive.
[0067] The coating is prepared in the same manner as in Example 1. 0.2 Sm 0.2 Ca 0.2 G 0.2 Dy 0.2 )AlO 3 The XRD spectrum of Figure 6 shown.
[0068] Wherein: the absorbing pigment is prepared according to the method described in Example 1, but its raw material is AO with a molar ratio of metal elements of 1:1 x Powder and BO x Powder, AO x For La 2 O 3 、Sm 2 O 3 , CaO, Gd 2 O 3 、Dy 2 O 3 Powder;BO x For Al 2 O 3 powder.
[0069] The coating performance indicators are shown in Table 4.
[0070] Table 4 Performance indicators
[0071]
[0072] Example 5 A high entropy perovskite-type absorption coating with ultra-wideband electromagnetic wave absorption characteristics is composed of the following raw materials: 14 g absorption pigment, 3.5 g filler, 35 g binder, 55 g ultrapure water, and 14 g auxiliary agent.
[0073] The coating is prepared in the same manner as in Example 1. 0.2 Sm 0.2 Ca0.2 G 0.2 Dy 0.2 )MnO 3 The XRD spectrum of Figure 7 shown.
[0074] Wherein: the absorbing pigment is prepared according to the method described in Example 1, but its raw material is AO with a molar ratio of metal elements of 1:1 x Powder and BO x Powder, AO x For La 2 O 3 、Sm 2 O 3 , CaO, Gd 2 O 3 、Dy 2 O 3 Powder;BO x MnO 2 powder.
[0075] The coating performance indicators are shown in Table 5.
[0076] Table 5 Performance indicators
[0077]
Claims
1. A high entropy perovskite type absorption coating with ultra-wideband electromagnetic wave absorption characteristics, characterized in that: The absorption coating is composed of the following raw materials in parts by mass: 8-16 parts of absorption pigment, 2-4 parts of filler, 20-40 parts of binder, 22-65 parts of ultrapure water, and 10-15 parts of additives; the absorption pigment is a high entropy perovskite ceramic pigment, and its molecular formula is ABO3, which is (La 0.2 Pr 0.2 Ca 0.2 Nd 0.2 Sm 0.2 )CrO3、(Sm 0.2 G 0.2 Ce 0.2 Nb 0.2 Dy 0.2 )CoO3、(La 0.2 Pr 0.2 Ca 0.2 Ce 0.2 G 0.2 )FeO3、(La 0.2 Sm 0.2 Ca 0.2 G 0.2 Dy 0.2 )AlO3、(La 0.2 Sm 0.2 Ca 0.2 G 0.2 Dy 0.2 )MnO3; the filler is one or more of calcium carbonate, porous powdered quartz, white carbon black, mica powder and bentonite, and the particle size is 50~200nm; the preparation method thereof comprises the following steps: ⑴Weigh according to the ratio; (2) After the ultrapure water, binder and additive are mixed and dispersed evenly, the absorption pigment and filler are added, and the mixture is stirred at a speed of 600-1200r / min for 60-100min by a high-speed disperser, and then dispersed and ground to a fineness of 15-30μm by a sand mill or a ball mill; finally, the mixture is filtered through a 100-200 mesh screen to obtain an ultra-wideband electromagnetic wave absorbing perovskite-type high entropy absorption coating; the absorption pigment is a powder material with a perovskite-type crystal structure and a diameter of 50-600 nm, and its absorption rate in the 0.3-2.5μm band of sunlight is not less than 0.87, and its absorption rate in the ultra-wideband band range of 0.3-16μm is not less than 0.85; the absorption pigment is prepared by the following method: AO with a molar ratio of metal elements of 1:1 x Powder and BO x The powder is used as the raw material for ball milling and mixing, and the mixture powder is obtained after drying and grinding; the mixture powder is calcined at high temperature in an air atmosphere, cooled and ground to obtain the AO x La2O3, Pr6O 11 , CaO, Nd2O3, Sm2O3 powder, the BO x Cr2O3 powder; or the AO x For Sm2O3, Gd2O3, Ce2O3, Dy2O3, Nb2O5 powder, the BO x CoO powder; or the AO x La2O3, Pr6O 11 , CaO, Ce2O3, Gd2O3 powder, the BO x Fe2O3 powder; or the AO x For La2O3, Sm2O3, CaO, Gd2O3, Dy2O3 powder, the BO x Al2O3 powder; or the AO x For La2O3, Sm2O3, CaO, Gd2O3, Dy2O3 powder, the BO x MnO2 powder; ⑶ Substrate surface treatment: Use quartz stone or brown corundum with a particle size of 1~5μm to sandblast the substrate surface to make the surface cleanliness of the substrate reach Sa 2.5~3.0 level requirements; (4) Under the condition of ambient temperature of 15-30℃ and relative air humidity below 85%, use 0.8MPa compressed air to spray ultra-wideband electromagnetic wave absorbing perovskite-type high entropy absorption coating on the treated substrate surface twice. After spraying, let it stand for 48 hours and then heat up in the furnace to cure, thus obtaining ultra-wideband electromagnetic wave absorbing coating.
2. A high entropy perovskite type absorption coating with ultra-wideband electromagnetic wave absorption characteristics as claimed in claim 1, characterized in that: The coating has a thickness of 50-100 μm, an operating temperature range of 800-1500°C, an absorptivity of not less than 0.95 in the 0.3-2.5 μm band of sunlight, and an absorptivity of not less than 0.92 in the 0.3-16 μm ultra-wide band.
3. A high entropy perovskite type absorption coating with ultra-wideband electromagnetic wave absorption characteristics as claimed in claim 1, characterized in that: The ball milling mixing conditions refer to using a planetary ball mill for wet ball milling, a ball milling speed of 300-500 r / min, a ball milling time of 5-12 hours, and a ball-to-material-water mass ratio of 2-5:1:
3.
4. A high entropy perovskite type absorption coating with ultra-wideband electromagnetic wave absorption characteristics as claimed in claim 1, characterized in that: The high temperature calcination conditions refer to a calcination temperature of 900-1500°C, a heating rate of 3-10°C / min, and a calcination time of 2-6 hours; the cooling method is one of furnace cooling, air quenching cooling, and liquid nitrogen quenching cooling.
5. The high entropy perovskite type absorption coating with ultra-wideband electromagnetic wave absorption characteristics as claimed in claim 1, characterized in that: The binder is at least one of rare earth phosphate, aluminum phosphate and titanium phosphate.
6. A high entropy perovskite type absorption coating with ultra-wideband electromagnetic wave absorption characteristics as claimed in claim 1, characterized in that: The auxiliary agent is a mixture of a leveling agent, a dispersant and a defoamer uniformly mixed in a mass ratio of 1:1:1 to 1:2:3; the leveling agent is one or two of Deqian 810 silicone leveling agent-polyether modified polysiloxane, AFCONA-3587-polyether modified silicone, and AFCONA-3085-polyether modified silicone; the dispersant is one or more of sodium oleate, carboxylate, sulfate ester salt, and sulfonate; the defoamer is one or two of TEGO Antifoam 3062 polyether defoamer, AFCONA-2035-fluorocarbon modified silicone, and AFCONA-2040-fluorocarbon modified silicone.
Citation Information
Patent Citations
Nano high-entropy protective coating suitable for water-cooled wall and preparation method of nano high-entropy protective coating
CN115650692A
Water-based high-entropy boride ceramic coating and preparation method thereof
CN117511262A